PREDISPOSISI KRIMINAL TINDAK PIDANA PERZINAHAN DAN ABORSI DALAM PELAKSANAAN PERATURAN PEMERINTAH NOMOR 61 TAHUN 2014 TENTANG KESEHATAN REPRODUKSI. - Siti Fatimah (Universitas Muhammadiyah Ponorogo, 2021)
This paper contains a discussion of predisposition or contradiction in laws and regulations governing the crime of adultery with the implementation of abortion. Adultery and abortion are criminal acts that are victimless in nature or crimes with mutual agreement and without victims. In positive Indonesian law, adultery is only considered a criminal act when one or both of the perpetrators are married people or in our society it is known as an affair or gathering. kebo. This is very contrary to Islamic law and laws that live in society or customary law as stated in the Pancasila. As a result, a pregnancy outside of wedlock or an unwanted pregnancy may result from this adulterous relationship. When a pregnancy outside of marriage occurs, the psychological condition of both parties is disturbed and eventually not a few decide to take the path of abortion, especially teenagers, even though at the risk of losing their life. Even though by law abortion is allowed, but even then it must be subject to rules, conditions and supervision. strictly carried out by competent parties as designated by law. The formulation of the article on adultery in Indonesian legislation is still unclear, especially for the act of adultery committed by two men and women who are neither married to any party. However, sexual behavior is risky or between other pre-marital sexual behavior according to Article 11 of Government Regulation no. 61 of 2014 concerning Reproductive Health to prevent and protect adolescents from these acts because it is clear that they have a bad impact both physically and psychologically. This is where there is a conflict between Indonesia's positive law, namely between Article 284 of the Criminal Code and Article 11 of Government Regulation no. 61 of 2014 concerning Reproductive Health. Meanwhile, the adultery article as mentioned above has been clearly stated in Article 240 of the Draft Criminal Code, but so it has not been ratified for certain reasons. Among the efforts to prevent the crime of adultery and abortion is the enforcement of the substance, structure and culture of law in Indonesia.